Layers of dendritic cell-mediated T cell tolerance, their regulation and the prevention of autoimmunity - Mayer, Christian T.; Berod, Luciana; Sparwasser, Tim D. (Frontiers in Immunology, 2012)
The last decades of Nobel prize-honored research have unequivocally proven a key role of dendritic cells (DCs) at controlling both T cell immunity and tolerance. A tight balance between these opposing DC functions ensures immune homeostasis and host integrity. Its perturbation could explain pathological conditions such as the attack of self tissues, chronic infections and tumor immune evasion. While recent insights into the complex DC network help to understand the contribution of individual DC subsets to immunity, the tolerogenic functions of DCs only begin to emerge. As these consist of many different layers, the definition of a ‘tolerogenic DC’ is subjected to variation. Moreover, the implication of DCs and DC subsets in the suppression of autoimmunity are incompletely resolved. In this review, we point out conceptual controversies and dissect the various layers of DC-mediated T cell tolerance. These layers include central tolerance, Foxp3+ regulatory T cells, anergy/deletion and negative feedback regulation. The mode and kinetics of antigen presentation is highlighted as an additional factor shaping tolerance. Special emphasis is given to the interaction between layers of tolerance as well as their differential regulation during inflammation. Furthermore, potential technical caveats of DC depletion models are considered. Finally, we summarize our current understanding of DC-mediated tolerance and its role for the suppression of autoimmunity. Understanding the mechanisms of DC-mediated tolerance and their complex interplay is fundamental for the development of selective therapeutic strategies, e.g. for the modulation of autoimmune responses or for the immunotherapy of cancer.